Membangun Islamic Human Resource Development (I-HRD) di Perguruan tinggi berlandaskan Worldview Ekonomi Islam - Rakhmad Agung Hidayatullah; Fuad Mas’ud; Amir Reza Kusuma; Usmanul Hakim (ITB AAS INDONESIA Surakarta, 2023)
The discussion on the Development of Islamic Human Resource Development (IHRD) is one of the contemporary issues that are interesting to study. In recent years alone, the intensity of research on the discourse on the development of IHRD in academic institutions has increased and shows an increasing presentation. Studies on the existence of IHRD in universities, educational institutions and many human empowerment institutions are carried out massively for the sustainability of the education system in the future. Therefore, in building IHRD with the foundation of the Islamic worldview, it is necessary to practice what is used as a form of employee development with a process that runs continuously. New problems, new procedures, new equipment, new restraints and new positions always arise in a dynamic organization, as for the steps that can be taken to create a higher education IHRD by means of mental, spiritual, educational and teaching worldview Islamic education and providing economic knowledge based on the Quran and Sunnah.